Penetration characteristics of pyramidal projectile into concrete target. (September 2020) - Dong, Heng; Wu, Haijun; Liu, Zihao; Gao, Xudong; Pi, Aiguo; Li, Jinzhu; Huang, Fenglei
Highlights: The penetration mechanisms of pyramidal projectiles into concrete are investigated. The relationship of the normal stress and the normal velocity on the surface of pyramidal projectile nose was modified. Triangular projectile has a slight penetration advantage over the circular projectile in low velocity range. Shear weakening effect plays a significant role in the penetration process of the pyramidal projectile. Abstract: The mechanisms governing penetration of pyramidal projectile into concrete medium were studied. The relationship of normal stress and normal velocity on the surface of the projectile nose was modified based on the assumption that the shape of the tunnel section is the same as that of the projectile. Then, in the low velocity range, a formula for predicting the final penetration depth of the pyramidal projectile is proposed, and the penetration ability of pyramidal projectiles with and without a shank is discussed. The results showed that the penetration depth decreases with the increasing side numbers of the projectile section shape, and the maximum depth of penetration corresponds to the triangular cross-section. In addition, the penetration processes of triangular and circular projectiles into concrete targets were simulated by employing the finite element software LS-DYNA. The Mises stress, tunnel shape, depth of penetration and velocity were investigated. It suggested the triangular projectile has a slight penetration advantage over the circular projectile when the penetration velocity is less than threshold velocity, and this advantage gradually disappears with the increase of impacting velocity. Finally, the shear weakening effect is used to explain the resistance characteristics of the triangular projectile in various velocity ranges, and a method to estimate the upper limit of threshold velocity is given by using the dynamic cavity expansion theory.